THE INFLUENCE OF XAVIERA COC COMPETENCE ON THE INTEREST IN LEARNING OF FEMALE STUDENTS OF THE FACULTY OF SOCIAL SCIENCES AND LAW, UNIVERSITAS NEGERI JAKARTA - Camelia, Lorra; Yoelianto, Haura Zahra; Wijanarko, Dewandaru Satryo; Rangga, Rangga; Sutiyono, Citra Amalia Putri; Ramadhan, M Rendy; Fikri, M; Allifiansyah, Sandy (Universitas Sang Bumi Ruwa Jurai, 2025)
This study aims to analyze the influence of Xaviera's appearance, knowledge, skills, and engagement as an influencer on the respondents' interest in learning and developing public speaking skills. A survey was conducted among 50 respondents to evaluate their views on various aspects of Xaviera's personal branding, such as the way she looks, the influence of content on understanding, and the impact of interaction with the audience. The results showed that most respondents gave a positive assessment of Xaviera's appearance and understanding of personal branding, with an average score close to the â€œStrongly Agreeâ€ category on various questions. In addition, Xaviera is also considered to have a high curiosity in exploring new things and being able to apply her analytical skills on various occasions. In terms of skills, the majority of respondents feel inspired by the content presented, and Xaviera's interaction with the audience is considered effective in supporting the understanding of the messages conveyed. Although there were a number of neutral respondents, the overall results showed that Xaviera had a significant positive impact on increasing the learning interest and public speaking skills of its audience. This research provides insight into the importance of consistency in personal branding and effective communication skills in inspiring and increasing audience engagement.Â Â